UV-B radiation enhances isoflavone accumulation and antioxidant capacity of soybean calluses - Wang, Mian; Liu, Guannan; Guo, Tianwei; Xie, Chong; Wang, Pei; Yang, Runqiang (Frontiers in Nutrition, 2023)
Isoflavones are a class of flavonoids that belong to a large family of polyphenols and synthesized predominantly in legume, and they play important roles including acting as antioxidant, preventing osteoporosis, reducing the risk of therosclerosis, and protecting against cardiovascular disease. This study focused on the accumulation and synthetic metabolism of isoflavone in soybean hypocotyl and cotyledon calluses under UV-B radiation. The results showed that UV-B radiation significantly up-regulated the gene expression of phenylalanine ammonia lyase (PAL), cinnamate-4-hydroxylase (C4H), 4-coumarate-CoA ligase (4CL), chalcone ketone synthase (CHS), chalcone isomerase (CHI) and isoflavone synthase (IFS), and enhanced their activity in soybean hypocotyl and cotyledon calluses. As a result, isoflavones content increased by 21.23% and 21.75% in soybean hypocotyl and cotyledon calluses, respectively. Among the isoflavones produced, malonyldaidzin was the dominant one in hypocotyl callus, while malonylglycitin and daidzein were the main isoflavones in cotyledon calluses. This study revealed that UV-B radiation induced isoflavone accumulation in soybean callues, which could be an efficient strategy to improve the nutritional value of food and produce high levels of bioactive secondary metabolites.